A study on urban-rural public bus passengers' demographic and trip characteristics in Peninsular Malaysia - Ponrohono, Zakiah; Bachok, Syahriah; Ibrahim, Mansor; Mohamed Osman, Mariana (Kulliyyah of Architecture and Environmental Design, IIUM, 2015)
This research highlights the urban-rural bus services gap in the selected settlements in Peninsular Malaysia. Four states are selected as case studies with Johor to represent the southern states, Penang to represent the northern states and for east-coast states, Pahang is selected. Meanwhile Perak is to represent a still developing state, which is yet to reach the advanced level of large conurbations. The main objectives are to evaluate the urban and rural bus service quality through passenger satisfaction survey. A total of 1130 survey questionnaire forms is distributed and collected. The results confirmed that there are gaps in urban and rural bus services based on the level of satisfaction among the passengers from different localities.